Menerapkan Makna Sakai Sambayan sebagai Nilai Kearifan Lokal Masyarakat Lampung dalam Pembelajaran Bahasa Indonesia: Perspektif Pendidikan Islam - Palyanti, Mega; Dessy Kemala Sari; M.Tegar Alvian Saputra; Ani Musriani (CV. Creative Tugu Pena, 2024)
This research aims to explain how the values of Islamic education are integrated into the Nima culture of the Pepadun community in Lampung. The form of Nemui Nyimah culture in the Tiyuh Panaragan community can be seen in hospitality activities, such as procedures or manners for visiting and receiving guests. The data analysis techniques researchers use are data reduction, data display and conclusion drawing/validation. Data was collected through participant observation, in-depth interviews, and note-taking. The findings show that